Thinking and Feeling - Romer, Paul M (American Economic Review, 2000)
Mistakes give us a window into the brain. Just as optical illusions help us understand visual information processing, mistaken choices help us understand decision-making. The mistakes described below suggest that economics can usefully segregate decision mechanisms into two broad categories - those based on thoughts and those based on feelings. Consideration of these mistakes suggests that economists will be better able to interpret the growing body of seemingly anomalous evidence about human behavior if they treat thoughts and feelings more symmetrically.